Elements of feminism in Pulitzer prize winners in the 2000s: A study on selected plays / Ahmad Kamal Basyah Sallehuddin - Ahmad Kamal Basyah , Sallehuddin (2018)

(untitled)
In this research, the researcher studies and analyses the elements of feminism in the plays that have won the prestigious Pulitzer Prize, ranging from the year 2000 until 2009, an era which is also known as Third Wave Feminism. First, the researcher identifies Pulitzer Prize-winning plays from 2000 until 2009, in order to locate elements of feminist ideas such as liberal feminism, cultural feminism and socialist feminism. Subsequently, the researcher analyses each selected feminist theory and how their ideas are incorporated in the themes and character and characterisation of the selected plays, where he later compares and contrast the influence of different feminist theories in the selected Pulitzer Prize winners in the new millennium. This is a qualitative research, where the researcher has conducted his research by studying the aspects of liberal feminism, cultural feminism and socialist feminism, as well as reading and comprehending the scripts of the case studies. The selected Pulitzer Prize winners in the ‘Drama’ category chosen by the researcher for this thesis are Proof by David Auburn, Doubt, A Parable by John Patrick Shanley, Rabbit Hole by David Lindsay-Abaire and August: Osage County by Tracy Letts. It is found that cultural feminism has the biggest influence in these selected plays, followed by liberal feminism and socialist feminism.